HETEROGENEOUS CATALYST CONVERSION 1,1,2-TRICHLOROETHANE TO CIS- AND TRANS- 1,2-DICHLOROETHEHES - Білокопитов, Ю. В.; Гаєвська, Т. А.; Драч, О. М. (Science-based technologies, 2009)
The 1,1,2-trichloroethane dehydrochlorination reaction to cis- and trans-1,2-dichloroethehes on aheterogeneous catalyst on the basis of FeCl3 and γ-Al2O3 is studied. On the basis of researches results andthermodynamic calculations the mechanism of reaction on the surface of this catalyst, which explains formationof major quantities of cis-isomer in comparison with a trans-isomer, is offered.